2023
DOI: 10.1002/adma.202302592
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Highly Efficient and Thermal‐Stable Polymer Solar Cells through Semi‐Alloy Acceptors Composed of a Hinge‐Like Dimer: A Versatile Doping Protocol

Abstract: The simultaneous improvement of power conversion efficiency (PCE) and thermal stability is a critical scientific challenge in advancing the commercial applications of polymer solar cells. To address this challenge, a dumbbell‐shaped dimeric acceptor, DT19, is successfully designed and synthesized. It is incorporated as a third component into the PM1:BTP‐eC9 system. This ternary strategy demonstrates a synergistic enhancement of the PCE and thermal stability of the host binary system. In particular, the PM1:BTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Similarly, Min et al recently designed a dumbbellshaped DiFREA, DT19, through connecting the N-2 position of benzotriazole ring in each monomer using a 1,6-hexyl linker. [35] By incorporating DT19 as a third component to binary systems, both device efficiency and thermal/mechanical stability were simultaneously improved. The main reason for this can be attributed to the formation of a semialloy model resulting from the interaction between DT19 and the host acceptor, thus leading to restraint on molecular movement under thermal stress.…”
Section: Minireviewsmentioning
confidence: 99%
“…Similarly, Min et al recently designed a dumbbellshaped DiFREA, DT19, through connecting the N-2 position of benzotriazole ring in each monomer using a 1,6-hexyl linker. [35] By incorporating DT19 as a third component to binary systems, both device efficiency and thermal/mechanical stability were simultaneously improved. The main reason for this can be attributed to the formation of a semialloy model resulting from the interaction between DT19 and the host acceptor, thus leading to restraint on molecular movement under thermal stress.…”
Section: Minireviewsmentioning
confidence: 99%
“…9–11 However, numerous studies have shown that the active layer of these P D :SMNFA photovoltaic systems generally presents a metastable state in the BHJ blend, showing poor operational and thermal stability. 8,12–15 Moreover, many tensile test analyses have exhibited that the corresponding P D :SMNFA system also has poor mechanical robustness, and its crack-onset strain (COS) is usually less than 5%. 15–18 In contrast, all-polymer solar cells (all-PSCs) composed of P D s and polymer acceptors ( P A s) are considered one of the most promising applications in flexible power systems owing to their excellent optical/thermal stability and flexible tensile properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Since the emergence of A-DA'D-A type non-fullerene acceptor (NFA), Y6, a milestone power conversion efficiency (PCE) of 15.7 % was achieved when paired with the polymer donor PM6, opening a new avenue for achieving highly efficient OSCs. [6] Although numerous efforts have been involved in developing Y6 derivatives to further boost the PCE of binary OSCs beyond 18 %, [7][8][9][10][11] a crucial issue of mismatch between the charge mobilities of the current efficient donors and acceptors, leading to severe charge accumulation and recombination and limiting further performance improvements. Since Y6 and its derivatives feature much stronger crystallinity than the polymer donor PM6, [12,13] they can form strong and ordered 3D interpenetrating network packing structure, endowing them with unique 3D transport properties and very high electron mobilities.…”
Section: Introductionmentioning
confidence: 99%